Synergistic Effects of Chemotherapy and Phototherapy on Ovarian Cancer Using Follicle-Stimulating Hormone Receptor-Mediated Liposomes Co-Loaded with SN38 and IR820 - Lina Pian; Bowen Zeng; Nuoya Wang; Shuangqing Wang; Hao Wu; Hongshuang Wan; Liqing Chen; Wei Huang; Zhonggao Gao; Dan Jin; Mingji Jin (MDPI AG, 2024)
We have developed an ovarian cancer-targeted drug delivery system based on a follicle-stimulating hormone receptor (FSHR) peptide. The lipophilic chemotherapeutic drug SN38 and the photosensitizer IR820 were loaded into the phospholipid bilayer of liposomes. The combination of chemotherapy and phototherapy has become a promising strategy to improve the therapeutic effect of chemotherapy drugs on solid tumors. IR820 can be used for photodynamic therapy (PDT), effectively converting near-infrared light (NIR) into heat and producing reactive oxygen species (ROS), causing damage to intracellular components and leading to cell death. In addition, PDT generates heat in near-infrared, thereby enhancing the sensitivity of tumors to chemotherapy drugs. FSH liposomes loaded with SN38 and IR820 (SN38/IR820-Lipo@FSH) were prepared using thin-film hydration-sonication. FSH peptide binding was analyzed using 1H NMR spectrum and Maldi-Tof. The average size and zeta potential of SN38/IR820-Lipo@FSH were 105.1 ± 1.15 nm (PDI: 0.204 ± 0.03) and −27.8 ± 0.42 mV, respectively. The encapsulation efficiency of SN38 and IR820 in SN38/IR820-Lipo@FSH liposomes were 90.2% and 91.5%, respectively, and their release was slow in vitro. FSH significantly increased the uptake of liposomes, inhibited cell proliferation, and induced apoptosis in A2780 cells. Moreover, SN38/IR820-Lipo@FSH exhibited better tumor-targeting ability and anti-ovarian cancer activity in vivo when compared with non-targeted SN38/IR820-Lipo. The combination of chemotherapy and photodynamic treatment based on an FSH peptide-targeted delivery system may be an effective approach to treating ovarian cancer.